Fuzzy Logic and Synchronous Reference Frame Controlled LVRT Capability Enhancement in Wind Energy System using DVR (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper gives a complete assessment of the various strategies used to decorate the skills of Low Voltage Ride Through (LVRT) of Double Fed Induction Generators (DFIG) primarily based wind turbine systems (WT). As the world is using about 20% to 25% of renewable energy from wind using DFIG primarily based Type-III WT machine is at once connected to the grid without the digital interface of power, as a result the terminal voltage or reactive electricity output can’t manage. Therefore, unique LVRT approaches based at the implementing additional active interface technologies had been proposed within this paper. Many approaches are now being researched to tackle this fault problem of low voltage. This report seeks to determine such working ways by bridging the gap in terms of the total adaptive performance, operative complexity of controllers and cost-effectiveness by analysing LVRT techniques for DFIG-based WECS. This study highlights the techniques to increase LVRT's ability to depend on the relationship setup in three main areas based on their grid integrations. In this work, FACT device connections are employed by WECS to evaluate its efficiency and advantage. MATLAB simulink is used to simulate the mathematical models of the entire system and examine its outcomes.